Off-target interactions in the CRISPR-Cas9 Machinery: mechanisms and outcomes - Lyubov Yu. Kanazhevskaya; Polina V. Zhdanova; Alexander A. Chernonosov; Vladimir V. Koval (Biochemistry and Biophysics Reports, 2025)
The in vivo editing of genetic information necessitates tools of unprecedented accuracy. CRISPR-Cas-based systems have emerged as leading technologies for precisely targeting the genome. The Cas9 endonuclease derived from Streptococcus pyogenes is the most commonly used instrument for targeted DNA cleavage. The development of engineered and chimeric Cas9 variants with enhanced activity and specificity has enabled not only the simple knockout of target genes but also the sophisticated engineering of the epigenome. This advancement has broadened the potential applications of CRISPR-Cas9 technology for the treatment of various disorders characterized by a combination of mutations, deletions, and duplications in the coding and non-coding regions of the genome. The inherent simplicity and predictability of the CRISPR-Cas9 targeting mechanism have led to an explosive growth in the development of prototype gene-editing drugs. However, their therapeutic application is still challenged by potential off-target effects. The erroneous editing of tumor suppressors and oncogenes could lead to adverse outcomes that mitigate the benefits of CRISPR therapy. The evolution of DNA-targeting technologies requires a comprehensive understanding of the mechanisms underlying CRISPR-Cas9 off-target binding and cleavage. The use of massive libraries of DNA targets and guide RNAs, coupled with high-throughput sequencing, contributes significantly to the analysis of mismatch tolerance. Nevertheless, the detection of ultra-low levels of off-target activity is hindered by the sensitivity limitations of current technologies. This review focuses on the mechanisms responsible for off-target interactions during CRISPR-Cas9-mediated gene editing. We discuss the influence of various factors, including nucleotide context, enzyme concentration, guide RNA structure, and the energetics of the RNA–DNA hybrid on mismatch tolerance in vitro and in vivo. Recent advances in the development of technologies for predicting off-target effects are briefly summarized. Particular emphasis is placed on the role of the Cas9 protein structure in the allosteric regulation of the specific and non-specific activity of the Cas9–sgRNA complex.